Biocompatible/Degradable Silk Fibroin:Poly(Vinyl Alcohol)-Blended Dielectric Layer Towards High-Performance Organic Field-Effect Transistor - Zhuang, Xinming (Nanoscale Res Lett, 2016)
Biocompatible silk fibroin (SF):poly(vinyl alcohol) (PVA) blends were prepared as the dielectric layers of organic field-effect transistors (OFETs). Compared with those with pure SF dielectric layer, an optimal threshold voltage of ~0 V, high on/off ratio of ~10(4), and enhanced field-effect mobility of 0.22 cm(2)/Vs of OFETs were obtained by carefully controlling the weight ratio of SF:PVA blends to 7:5. Through the morphology characterization of dielectrics and organic semiconductors by utilizing atom force microscopy and electrical characterization of the devices, the performance improvement of OFETs with SF:PVA hybrid gate dielectric layers were attributed to the smooth and homogeneous morphology of blend dielectrics. Furthermore, due to lower charge carrier trap density, the OFETs based on SF:PVA-blended dielectric exhibited a higher bias stability than those based on pure SF dielectric. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-016-1660-x) contains supplementary material, which is available to authorized users.